The management of mercury from dental amalgam in wastewater effluent. Issue 1 (1st January 2021) - Fairbanks, Simon D.; Pramanik, Sumit Kumar; Thomas, Jim A.; Das, Amitiva; Martin, Nicolas
ABSTRACT: Dental restorative material mercury amalgam - which is composed of approximately 50% mercury - has been used for centuries. Although many alternatives to amalgam are available or under development, its mechanical, inert, durable and cost-effective properties mean that globally it is still the predominant filling material in dental practices. Current expert opinion is that, in a clinical setting, amalgam is safe and well tested, with clinical studies revealing no adverse health effects to amalgam fillings. Nevertheless, in line with the Minamata convention, the use of mercury amalgam is being phased down. More significantly, although waste disposal methods have developed considerably, the ultimate environmental fate of dental mercury is not fully delineated; furthermore, the amount of mercury in the environment from historical poor practice is still largely unknown. In this review an overview of how mercury is managed and disposed of in modern dental clinics is provided. Recent best estimates for mercury consumption in dental applications are discussed and compared to total global mercury consumption. The ultimate environmental sinks for the metal are identified and the methods currently employed to process products that are highly deleterious to the environment and human health are described. With a focus on environmentally mobile and highly toxic alkyl mercury compounds, some of the possible environmental implications that could occur with poor waste management are also outlined. GRAPHICAL ABSTRACT: UF0001